Pengaruh Edukasi Kesehatan Terhadap Perilaku Personal Hygiene Lansia Di Desa Tijue Kecamatan Pidie Kabupaten Pidie - Kartika; Syamsul Idris; Yuriansah (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
The aging process in the elderly results in a decline in physiological function that directly impacts self-care abilities and, if suboptimal, risks triggering skin infections and reducing quality of life. Health education is needed as a crucial promotive strategy to increase awareness and understanding of the elderly in implementing clean and healthy living behaviors independently. This quantitative study aims to analyze the effect of health education on changes in personal hygiene behavior in the elderly. The study design used a one-group pretest-posttest conducted from February to June 2026. A sample of 35 respondents was selected through a purposive sampling technique. Data were obtained through questionnaires and observations, then analyzed using the Wilcoxon Signed Ranks Test. The results showed that before education, the majority of respondents had adequate behavior (62.9%). After the educational intervention through leaflets and demonstrations, there was a significant increase with 82.9% of respondents being categorized as good. Statistical analysis produced a p-value of 0.000 (p < 0.05) with a Z-value of -5.162, thus it can be concluded that the intervention had a significant impact on respondents' behavior. It was concluded that there was a significant influence of providing health education on improving the personal hygiene behavior of the elderly in Tijue Village, Pidie District. It is recommended to make personal hygiene education a routine program in elderly health services.